New Public Management, Austerity, and the Alienation of the Medical Profession in France - Simonet D (Dove Medical Press, 2024)
Daniel Simonet Department of Management, Strategy and Entrepreneurship, American University of Sharjah, School of Business and Management, Sharjah, United Arab EmiratesCorrespondence: Daniel Simonet, Email dsimonet@aus.eduAbstract: In the last twenty years, France has gone through health policy changes that are perceived as paradigm shifts. After briefly describing the reforms driven by the new public management and the subsequent re-centralization of the French health system for budgetary purposes, it appears that those reforms had outcomes below expectations. The regrouping of policy decisions within the Regional Health Agencies and the rise of a French Welfare elite weakened the medical profession. Blame-shifting strategy, political dilution, and spatial inequality linger. The COVID-19 epidemic highlights those limitations. The negative societal and political impact of failed public reforms is increasingly evident.Keywords: France, public administration, health reform, new public management